2012
DOI: 10.1103/physrevlett.109.247605
|View full text |Cite
|
Sign up to set email alerts
|

Giant Reduction of InN Surface Electron Accumulation: Compensation of Surface Donors by Mg Dopants

Abstract: Extreme electron accumulation with sheet density greater than 10(13) cm(-2) is almost universally present at the surface of indium nitride (InN). Here, x-ray photoemission spectroscopy and secondary ion mass spectrometry are used to show that the surface Fermi level decreases as the Mg concentration increases, with the sheet electron density falling to below 10(8) cm(-2). Surface space-charge calculations indicate that the lowering of the surface Fermi level increases the density of unoccupied donor-type surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…[14][15][16][17] So far, the experimental results together with theoretical conclusions indicate that the occurrence of electron accumulation at InN surfaces strongly depends on surface reconstructions, 4,18 the formation of In-adlayers, [18][19][20] as well as adsorbates 13,20 or dopants. 21 All these mechanisms seem to be connected with the presence of characteristic occupied and unoccupied surface states that determine the surface Fermi level position and thereby the surface electron accumulation. [5][6][7] Surface states were already experimentally observed for In-polar and Npolar InN films, 4,13,22 while no measurements for nonpolar InN exist.…”
mentioning
confidence: 99%
“…[14][15][16][17] So far, the experimental results together with theoretical conclusions indicate that the occurrence of electron accumulation at InN surfaces strongly depends on surface reconstructions, 4,18 the formation of In-adlayers, [18][19][20] as well as adsorbates 13,20 or dopants. 21 All these mechanisms seem to be connected with the presence of characteristic occupied and unoccupied surface states that determine the surface Fermi level position and thereby the surface electron accumulation. [5][6][7] Surface states were already experimentally observed for In-polar and Npolar InN films, 4,13,22 while no measurements for nonpolar InN exist.…”
mentioning
confidence: 99%
“…Significant reduction of a SEAL by compensating bulk acceptors has been previously demonstrated in InN by Mg doping [23]. Previous studies [24,25] have shown that acceptors like Ni and Mg have a compensating effect on the bulk electron transport of In 2 O 3 .…”
Section: Introductionmentioning
confidence: 90%
“…Subsequent studies have found that the contribution from the surface charge accumulation to the InN free electron concentration arises as a consequence of the band structure associated with InN, and thus, remains an intrinsic feature of this material. [17][18][19] Most recently, Linhart et al 20 found that the incorporation of magnesium dopants near the surface compensates for this large surface charge accumulation. In terms of the unintentional bulk dopants, hydrogen and oxygen have emerged as the leading candidates.…”
Section: Introductionmentioning
confidence: 98%